Investigation of anti-cancer activity of linear and aldehyde-activated levan from Halomonas smyrnensis AAD6(T) - TOKSOY ÖNER, EBRU (ELSEVIER, 2014)
The main aim of this study was to investigate the potential role of levan polysaccharide in developing polysaccharide-based anticancer therapeutics. Moreover, by periodate oxidation, chemically modified forms of levan harboring increasing amounts of aldehyde groups were obtained and characterized. All the samples were found to be biocompatible when treated with the mouse fibroblast cell line L929. Anticancer activities of levan and its derivatives were investigated in A549 (human lung adenocarcinoma), HepG2/C3A (human liver hepatocellular carcinoma), AGS (human gastric adenocarcinoma), and MCF-7 (human breast adenocarcinoma) cell lines and were found to depend on the dose as well as on the cell type. The observed decrease in cancer cell viability was shown to be due to apoptosis via luminogenic-based caspase-3/7 activity assay. This study established the high potential of these levan-based polymers in developing polysaccharide-based nanocarrier systems for anti-cancer drugs. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Levan; Anti-cancer activity; Animal cell culture; Biomedical; Fructose; Tissue cell culture; ANTITUMOR-ACTIVITY; IN-VITRO; POLYSACCHARIDE; ANTIOXIDANT; FILMS